Trans-oral robotic surgery for oropharyngeal cancer: implications for pathologists. Issue 4 (April 2020) - Robinson, Max; O'Hara, James; Siddiq, Somiah; Jones, Terry M.; Paleri, Vinidh; Sandison, Ann; Thavaraj, Selvam
Abstract: Trans-oral robotic surgery (TORS) was approved by the FDA in 2009 and over the past decade head and neck surgeons have adopted the technology for the benefit of their patients. Whilst the surgical methods have evolved, there has been little consideration about the pathological assessment of the specimens and a lack of understanding around the oncological principles that underpin minimally invasive surgical techniques in the head and neck region. This article will highlight the issues encountered during the reporting of TORS specimens. The challenges include identifying anatomical boundaries, block selection, assessment of resection margins, the use of intra-operative frozen sections, the assessment of tongue base mucosectomies for patients with head and neck cancer of unknown primary, and TORS for recurrent disease. The article will conclude with emerging innovations, including i-Knife, narrow band imaging and the potential of step serial sections to identify sub-clinical HPV-related oropharyngeal squamous cell carcinomas.